FORMATION OF CREATIVE QUALITIES OF FUTURE TEACHERS IN THE PROCESS OF PROFESSIONAL TRAINING - V.V. Ivanova (Academy of Cognitive and Natural Sciences, 2009)
This article deals with the question of formation of students' creative abilities. The author shows the specific conditions of students' creative abilities forming during professional training.